IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TEKNIK THINK PAIR SQUARE (TPS) TERHADAP HASIL BELAJAR PKN PESERTA DIDIK DI KELAS VII SMP NEGERI 2 BAMBANG KABUPATEN MAMASA - Suhaeba Nur (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2016)
The purpose of this study to find out; differences in learning outcomes Civics learners using a model cooperative learning techniques Think Pair Square (TPS) with those using model lectures in class VII SMP Negeri 2 Bambang Mamasa, with the kind of experimental research, with a sample of students of class VII SMP Negeri 2 Bambang totaling 46 people. Data collection techniques used were observation sheet, study and documentation of test results. The results showed that the average value of learning outcomes in the classroom civics experiment on stage prettest of 61.46 and a middle category with the percentage as much as 79.2% and the posttest phase values obtained an average of 78.12 and in the category high percentage of as much as 95.8%. While the average value of learning outcomes in the classroom Civics pretest control on stage at 61.14 and the middle category with the percentage as much as 72.7% and the posttest phase values obtained an average of 71.82 and at high category with a percentage 63.4%.